Repeat the remarkable : how strong leaders overcome business challenges to take their performance to the next level - Holley, Perry M. (New York : McGraw-Hill Education, 2014)
"Learn how IBM has overcome its toughest challenges--and how you can replicate iconic company's success. Over the past 100 years, the IBM Corporation has survived several recessions and innumerable twists and turns in the global technology market. And even in an economy of global recession, this icon continues to repeat remarkable performance after remarkable performance--reinventing the meaning of corporate sustainability, employee loyalty and value-added leadership--and followed by memorable customer service. Repeat the Remarkable reveals the leadership lessons of a top IBM leadership development trainer. In it, Holley gives you the tools to tap into your own personal success--so you can lead your company to remarkable and repeatable performances. Perry Holley is program director, IBM Leadership Development"--
Includes bibliographical references (pages 231-233) and index.
Keywords: Leadership; Management; BUSINESS & ECONOMICS / Leadership